SANDUR: Sandal Daur Ulang yang Ramah Lingkungan untuk Memperkaya Variasi Produksi Home Industri Sandal di Dukuh Gambiran - Muhamad Soleh Sholachudin; Wirawan Fadly; Budiyono Saputro (Jurnal Pemberdayaan Masyarakat, 2022)
Assistance that focuses on strengthening assets owned by the Home Slipper Industry UMKM in Gambiran Hamlet through the use of plastik waste and used cardboard because there is a lot of plastik waste in the village and it makes the environment dirty. This mentoring process is in the form of training for sandal MSME owners by recycling used plastik and cardboard waste so that they become goods or crafts that have a selling value. This is so that business owners can still produce sandals, which is a solution during a pandemic to reduce production costs. This assistance uses an asset or strength approach which is commonly referred to as the ABCD method. This method uses the utilization of the assets or potentials of the community. This asset-based approach is very suitable to be applied from existing problems, so that the use of plastik waste for sandals is a solution amidst the difficulties of the COVID-19 pandemic.